A SHORT HISTORY OF FORT WYNYARD. TABLE BAY DEFENCES - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Relatively Iittle has been written about the history of the coastal defences of Table Bay. Although K. W. Maurice-Jones's book The History of Coast Artillery in the British Army1 appeared in 1959 and articles about South Africa's coast gunners were published from time to time. This is hardly surprising since they remained operational until 1955 when the South African Mari ne Corps was disbanded and the batteries were transferred to the South African Navy for care and maintenance.